Analisis Learning Trajectory Siswa dalam Mengonstruksi Pengetahuan Melalui Pemecahan Masalah Matematika Ditinjau dari Adversity Quotient - Syifaurrahmadania Syifaurrahmadania; Kamid Kamid; Syamsir Sainuddin (Media Pendidikan Matematika, 2026)
This study aimed to analyze students’ learning trajectories in constructing knowledge through mathematical problem solving viewed from adversity quotient (AQ). The problem context used ethnomathematics, namely the Putro Retno traditional Jambi wedding dais, connected to number patterns, particularly arithmetic sequences. This qualitative case study involved three Grade VIII students of SMP N 15 Muaro Jambi, selected purposively based on AQ categories: climber (S1), camper (S2), and quitter (S3). Data were collected through an AQ questionnaire, information-observation sheets, written problem-solving tests, think-aloud activities, and interviews. The data were analyzed through reduction, display, and conclusion drawing. The findings revealed different learning trajectories across AQ categories. S1 showed the most complete trajectory in the stages of problem solving. This student was able to construct knowledge through both assimilation and accommodation and adjust thinking when inconsistencies appeared. S2 generally followed the predicted trajectory. This student understood the problem and chose the strategy considered easiest, but did not recheck the solution. Accommodation occurred when S2 encountered inconsistent information. In contrast, S3 showed a trajectory dominated by assimilation. This student understood the problem only from visible information, did not correct errors, did not review the answer, and was not yet able to adjust thinking when inconsistencies emerged, resulting in disequilibrium. These findings indicate that AQ categories are associated with differences in students’ learning trajectories when constructing knowledge through mathematical problem solving. The study also suggests that teachers should consider students’ persistence and adaptive responses when designing problem-based mathematics learning in contextual and culturally meaningful classroom activities.